The Tradition of Short Stories in Bihar and Its Development Journey: बिहार में लघुकथा परंपरा और उसकी विकास यात्रा - Kumari, Sangeeta (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This article presents a comprehensive study of the tradition of short stories (laghukatha) in Bihar and its developmental journey. It highlights the contributions of various authors from the early stages of the short story form to the contemporary period. The article mentions the creative efforts of prominent literary figures such as Jagdish Kashyap, Sukesh Sahni, Dr. Satishraj Pushkarna, and Dr. Mithilesh Kumari Mishra, who played a significant role in establishing the short story as a powerful literary genre. It also discusses how short stories emerged as an expressive medium reflecting the social, political, and cultural milieu, thereby gaining a unique identity. The evolution in the structure, themes, and style of short stories from the late 19th century to the 21st century has also been explored. This article serves as an important document for understanding the chronological development of the short story form. Abstract in Hindi Language: यह लेख बिहार में लघुकथा परंपरा और उसके विकास की यात्रा का विस्तृत अध्ययन प्रस्तुत करता है। इसमें लघुकथा विधा के प्रारंभिक चरण से लेकर समकालीन काल तक के लेखकों एवं उनके योगदान को रेखांकित किया गया है। लेख में जगदीश कश्यप, सुकेश साहनी, डॉ. सतीशराज पुष्करणा, डॉ. मिथिलेश कुमारी मिश्र सहित अनेक साहित्यकारों के रचनात्मक प्रयासों का उल्लेख है जिन्होंने लघुकथा को एक सशक्त विधा के रूप में स्थापित किया। लेख में यह भी बताया गया है कि कैसे लघुकथा ने सामाजिक, राजनीतिक और सांस्कृतिक परिवेश को अभिव्यक्त करने का माध्यम बनकर नई पहचान बनाई। १९वीं सदी के अंत से लेकर २१वीं सदी तक लघुकथा की संरचना, विषयवस्तु और शैली में आए परिवर्तनों को दर्शाया गया है। यह लेख लघुकथा के विकास क्रम को समझने हेतु एक महत्त्वपूर्ण दस्तावेज के रूप में कार्य करता है। Keywords: लघुकथा, बिहार, हिंदी साहित्य, साहित्यिक परंपरा, समकालीन लेखन, सामाजिक संदर्भ